2010
DOI: 10.1002/chem.201001450
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiafulvalene‐amido‐2‐pyridine‐N‐oxide as Efficient Charge‐Transfer Antenna Ligand for the Sensitization of YbIII Luminescence in a Series of Lanthanide Paramagnetic Coordination Complexes

Abstract: The tetrathiafulvalene-amido-2-pyridine-N-oxide (L) ligand has been employed to coordinate 4f elements. The architecture of the complexes mainly depends on the ionic radii of the lanthanides. Thus, the reaction of L in the same experimental protocol leads to three different molecular structure series. Binuclear [Ln(2)(hfac)(5)(O(2)CPhCl)(L)(3)]·2 H(2)O (hfac(-)=1,1,1,5,5,5-hexafluoroacetylacetonate anion, O(2)CPhCl(-)=3-chlorobenzoate anion) and mononuclear [Ln(hfac)(3)(L)(2)] complexes were obtained by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 158 publications
(58 reference statements)
5
45
1
Order By: Relevance
“…In fact the lanthanides are exciting due to their specific luminescence, in addition to their magnetic characteristics. It has been demonstrated that the IR luminescence of the Yb III ion can be sensitised by the antenna effect when the charge transfers of the TTF‐based ligands are activated 11a,e. In our case, the TTF derivatives perform several roles and can act not only as electroactive ligands but also as structural agents to isolate the magnetic centres.…”
Section: Introductionmentioning
confidence: 79%
“…In fact the lanthanides are exciting due to their specific luminescence, in addition to their magnetic characteristics. It has been demonstrated that the IR luminescence of the Yb III ion can be sensitised by the antenna effect when the charge transfers of the TTF‐based ligands are activated 11a,e. In our case, the TTF derivatives perform several roles and can act not only as electroactive ligands but also as structural agents to isolate the magnetic centres.…”
Section: Introductionmentioning
confidence: 79%
“…The two Dy III ions are bridged by two L 1 ligands in a μ 2 (η 1 ,η 2 ) coordination mode, which could be suitable for the transmission of significant magnetic interactions. Notably, for each monoanionic L 1 ligand coordinated to the lanthanide centre, one tta – anion is removed to guarantee the formation of a neutral dinuclear species 5c. The TTF cores of the L 1 and L 2 ligands are neutral.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the most important difference between the electronic spectra of free L and 1 was the intensity of the absorption band centered near 300 nm. This absorption band originated from the π-π* excitations localized on the hfac − anions [25]. absorption band centered near 300 nm.…”
Section: Absorption Spectroscopymentioning
confidence: 98%
“…absorption band centered near 300 nm. This absorption band originated from the π-π* excitations localized on the hfac − anions [25]. …”
Section: Absorption Spectroscopymentioning
confidence: 99%